Peningkatan Literasi Digital Santri Melalui Pelatihan Dasar Komputer di Dayah Darul Muta’alimin - Jamali; Zubaili (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This community service program was designed to enhance the digital literacy of students (santri) at Dayah Darul Muta’alimin, located in Dusun Lhok Paya, Gampong Bukit Pala, East Aceh Regency. The training took place from February 10 to 13, 2025, involving 30 participants aged 15 to 20 years. The objective was to provide santri with essential computer skills to support their learning process and prepare them for the demands of the digital age. The training materials covered basic computer hardware, Microsoft Office applications (Word), introductory internet usage, and digital ethics. The method employed was a hands-on, learning by doing approach, combined with pre-tests and post-tests to measure learning outcomes.The results showed a significant improvement in participants’ abilities, with an average increase of 42% in post-test scores. Participants demonstrated practical skills such as typing, formatting documents, creating data tables, and developing simple presentations. Moreover, the program succeeded in fostering awareness of responsible and ethical technology use. Overall, the activity had a positive impact on the participants’ digital competencies and confidence in using technology for educational and personal development. It is recommended that similar programs be continued and expanded, with the potential to integrate digital literacy as a core component of pesantren education.